Inadequate Dietary Nutrient Intake in Patients With Rheumatoid Arthritis in Southwestern Sweden: A Cross-Sectional Study - Turesson Wadell, Anna; Bärebring, Linnea; Hulander, Erik; Gjertsson, Inger; Lindqvist, Helen M.; Winkvist, Anna (Frontiers in Nutrition, 2022)
Background: Patients with rheumatoid arthritis (RA), who suffer from impaired physical function and fatigue, may have difficulties with grocery shopping and preparing meals. Also, to improve symptoms, patients often experiment with diets but seldom consult a dietitian. Although this could lead to a nutritiously deprived diet, an up-to-date, thorough description of the nutrient intake in Swedish patients with RA is absent. Here, we investigated the habitual dietary energy- and nutrient intake in patients with RA living in southwestern Sweden. Methods: Three-day food records performed at two time points during the ADIRA (Anti-inflammatory Diet In Rheumatoid Arthritis) trial, were used. The intake of energy and nutrients was analyzed using The Swedish Food Composition Database. Results: Sixty-two participants (50 females, 12 males) were included in the study, where 18 participants completed one 3-d food record and 44 participants completed two 3-d food records. Median (IQR) intake of total fat was above or in the upper range of recommendations (females: 37.1 [32.5, 41.7] energy percent (E%), and males: 40.3 [37.5, 42.9] E%). Median (IQR) intake of saturated fatty acids exceeded recommendations (females: 14.9 [12.5, 17.0] E% and males: 15.4 [12.2, 17.0] E%), while median (IQR) carbohydrate- and fiber intakes were below recommendations (females: 41.7 [36.3, 45.4] E% and 17.2 [12.8, 20.9] g, respectively, and males: 38.8 [35.2, 40,3] E% and 18.5 [15.7, 21.0] g, respectively). The reported intake of other macronutrients was in line with recommendations. For several micronutrients, e.g., vitamin A and D, folate, and calcium, median intake was below recommended intake. Vitamin A intake was especially low and did not reach lower intake level (LI) for 14% and 17% of females and males, respectively. For females, about 10% did not reach LI for vitamin D, calcium, and riboflavin. Conclusions: We found that patients with RA residing in southwestern Sweden reported a high intake of saturated fatty acids, and low intake of fiber and several micronutrients. Trial registration: NCT02941055 https://clinicaltrials.gov/ct2/show/NCT02941055?term=NCT02941055&draw=2&rank=1.